1999
DOI: 10.1023/a:1008910718446
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The rate of in vivo degradation and level of bioactivity of bioactive glasses are composition dependent [1]. By altering bioactive glass composition, the rate of resorption can be controlled. The network connectivity of a glass can be used to predict various physical properties of the glass including its solubility and, hence, its bioactivity [2]. Glass solubility increases as network connectivity is reduced. Glasses in the soda-lime phosphosilicate system were studied. The initial choice of composition was ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(74 citation statements)
references
References 2 publications
3
66
0
5
Order By: Relevance
“…This phenomenon appears to be a characteristic of bioactive glasses. It has been observed in a number of previous studies [10,34] and is related to the particle size effects on heat transfer [35].…”
Section: Characterisation Of Glassesmentioning
confidence: 71%
“…This phenomenon appears to be a characteristic of bioactive glasses. It has been observed in a number of previous studies [10,34] and is related to the particle size effects on heat transfer [35].…”
Section: Characterisation Of Glassesmentioning
confidence: 71%
“…** Fig It is suggested that magnesium suppresses crystallisation. Crystallisation of a bioactive glass is known to inhibit its bioactive properties due to the lower reactivity of the crystalline state and increased resistance to the ion exchange reaction [59].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…A Figura 6 24 Para comprovar este fato, tanto o vidro como a espuma foram imersos em água durante 28 dias a 37 ºC em estufa. Foi possível observar um aumento no valor de pH de 10 para 12,4, o que comprova o consumo de H + do meio.…”
Section: Figura 2 Curvas De Retração Linear (Rl) E De Derivada Primeunclassified